An analysis of a rural hospital's investment decision under different payment systems - Xidong Guo (University College Dublin, UCD School of Economics, 2023)
Healthcare payment systems influence to a great extent the hospitals' investment decision and thereby, their ability to treat patients. A payment system is optimal provided it incentivises hospitals to undertake an investment level that is appropriate, when considering treatment costs, patients' welfare and the possible externalities generated. In this paper I focus on a hospital in a rural community where the frequency of utilisation of expensive equipment is possible low, and where patients may incur transfer costs. Considering both, a rural and an urban hospital, I identify the first-best investment level of a rural hospital and compare it with the investment levels arising from two payment systems: The Fee-for-service (FFS) system and the Diagnosis-Related Groups (DRG) system. Under the FFS system, the investment only depends on the characteristics of the rural hospital while it depends on characteristics of both hospitals under the DRG system. I show that the DRG performs better than the FFS system when the rural hospital has a lower treatment cost than the urban hospital. When the rural hospital has a higher cost, the FFS system is superior when the HA intends to motivate investment. Lastly, I show that incorporating location factor into the DRG pricing formula to incentivise the rural hospital is effective only when it has a higher treatment cost
Keywords: C72; H51; I18; L13; L78; 330; Healthcare payment system; rural hospitals; hospital investment; externality